2005
DOI: 10.1029/2005gl023908
|View full text |Cite
|
Sign up to set email alerts
|

Decadal variability in the Arctic Ocean shown in hydrochemical data

Abstract: [1] The recent distribution of Russian hydrochemical data collected from the Arctic Basin provides useful information on ocean interior variabilities. Among various chemical components, silicate is the most valuable for showing the boundary between the silicate-rich Pacific Water and the opposite Atlantic Water. Here, it is assumed that the silicate distribution receives minor influence from seasonal biological productivity and Siberian Rivers outflow. It shows a clear maximum around 100-m depth in the Canada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Here, we should remark that wind forcing induces mainly interannual fluctuations (e.g., Rudels 2012;Ikeda 2014;Yoshizawa et al 2015). Since the observation dates of the HAAC dataset are biased towards the late 1970s, it is possible that the upper ocean of the Canada Basin was affected by a weaker polar vortex (a cyclonic atmospheric circulation around the North Pole) due to low Ekman divergence during the late 1970s (Ikeda et al 2005).…”
Section: Results For the Water Mass Distribution In The Upper Ocean Amentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we should remark that wind forcing induces mainly interannual fluctuations (e.g., Rudels 2012;Ikeda 2014;Yoshizawa et al 2015). Since the observation dates of the HAAC dataset are biased towards the late 1970s, it is possible that the upper ocean of the Canada Basin was affected by a weaker polar vortex (a cyclonic atmospheric circulation around the North Pole) due to low Ekman divergence during the late 1970s (Ikeda et al 2005).…”
Section: Results For the Water Mass Distribution In The Upper Ocean Amentioning
confidence: 99%
“…A couple of studies have used HAAC data along with numerical models. Ikeda et al (2005) used silicate data to derive the vertical motion of the upper halocline on a decadal timescale in response to the Northern Annular Mode (NAM), which is the first empirical orthogonal component, and found a steep positive gradient at around 300 m depth. Ikeda (2014) examined horizontal movement in the Arctic Ocean and found that the dominant atmospheric mode shifted from the NAM to the Arctic Dipole Mode (ADM), the second empirical orthogonal component, around the year 1990.…”
Section: Introductionmentioning
confidence: 99%
“…The polar vortex was a major cyclonic circulation in the Arctic atmosphere and had more significant decadal oscillations than the trend (Thompson & Wallace 1998). The geochemical data indicated that vertical motion in the ocean interior was responding to the variable polar vortex (Ikeda et al 2005).…”
mentioning
confidence: 96%